Faktor yang Mempengaruhi Keputusan Mahasiswa Berwisata ke Luar Negeri - I Putu David Adi Saputra; Made Antara; I Nyoman Sudiarta (JURNAL MASTER PARIWISATA, 2022)
Tourism and hospitality is one of the largest service industries in the world that has an influence on global economic growth. Various factors can influence a person to travel There is a phenomenon that shows the increasing number of tourist visits abroad. This indicates that the need to travel by Indonesian tourists is getting higher. Indonesian tourists who travel both home and abroad consist of various ages and occupations. The purpose of this study was to analyze the pull and push factors that influence the decision of Bali tourism students to travel abroad. This study uses survey research methods with a total of 130 respondents. Researchers used factor analysis techniques and were processed using the IBM SPSS V.26 for Windows program. The results of the analysis of the results included that the motivation that became the push factors of Bali tourism students traveling abroad was to want to show prestige or lifestyle, while the motivation that became the pull factors of Bali tourism students traveling abroad was because the location, products, and services in the tourist destination area that can be accessed easily. Keywords: Push Factors, Pull Factors, Travel Decisions.